How to Build Scalable & Sustainable D2C Brand in Web 3.0? - Sandhuu, Preet (Digital Repository of Theses, 2025)
The rise of Web 3.0, characterized by blockchain, decentralization, and tokenization, is transforming the Direct-to-Consumer (D2C) brand landscape. This study explores the strategic and technological frameworks essential for building scalable and sustainable D2C brands. Employing a mixed-methods research approach, the study identifies key success factors and consumer attitudes toward these brands. While descriptive statistical methods were utilized to analyze quantitative data, inferential statistics were applied, including regression and correlation analysis, to uncover relationships between key variables. Findings highlight the role of blockchain in enhancing supply chain transparency, tokenization in fostering customer engagement, and decentralization in enabling financial models. The study concludes with strategic recommendations for integrating Web 3.0 technologies to enhance brand trust, transparency, and consumer empowerment. Findings indicate that blockchain technology enhances supply chain transparency, ensuring authenticity, ethical sourcing, and fraud prevention—factors that significantly contribute to consumer trust. Additionally, tokenization fosters customer engagement through digital loyalty programs and ownership models, while decentralized finance (DeFi) enables new financial models that enhance brand accessibility and operational efficiency. However, challenges such as regulatory uncertainty, technological adoption barriers, and the need for consumer education persist. The study concludes that D2C brands must integrate Web 3.0 technologies strategically to remain competitive, emphasizing trust, transparency, and consumer empowerment. A proposed framework highlights best practices for implementing blockchain, decentralization, and tokenization to enhance customer experience and brand sustainability. These insights provide valuable guidance for businesses, policymakers, and consumers navigating the evolving digital commerce landscape.